THỬ NGHIỆM VIỆC MỞ RỘNG BÀI TOÁN NGƯỢC XÁC ĐỊNH HÌNH DẠNG VẬT THỂ GÂY DỊ THƯỜNG TỪ ĐỂ XÁC ĐỊNH ĐỘ SÂU MÓNG TỪ TRÊN MỘT SỐ TUYẾN ĐO THUỘC KHU VỰC MIỀN TRUNG THỀM LỤC ĐỊA VIỆT NAM - Thanh, Đỗ Đức; Hằng, Nguyễn Thị Thu (Vietnam Journal of Science and Technology, 2012)
ATEMPT THE IMPROVEMENT OF INVERSION OF MAGNETIC ANOMALIES OF TWO DIMENSIONAL POLYGONAL CROSS SECTIONS TO DETERMINE THE DEPTH OF MAGNETIC BASEMENT IN SOME DADA PROFILE OF MIDDLE OFF SHELF OF VIETNAM In this paper the improvement of inversion of magnetic anomalies of two – dimensional polygonal coss sections is presented to determine the depth of magnetic basement. Based on this method, a computer programme is made a code to apply to determine some data profiles in the middle off shelf of Vietnam. Received results of the application shows highly exact and stable of the the methods.